Caracterização da fragilização pelo fósforo e efeito da adição de sílica durante o processo de laminação a quente de um aço C-Mn - Lívia Ananias dos Santos Mangualde (2020)
The various types of steel that was produced have a high variety of deleterious elements in their composition, the phosphorus can be one of the main impurities that strongly influence the quality. In this work the embrittlement caused by phosphorus during hot rolling of C-Mn steel pipes was characterized. The steel was produced in an electric steelmaking and hot-rolled using two types of deoxidizers that contain phosphorus in their composition: one containing 70% phosphate and the other 80% phosphate and 3% of silica (SiO2). After hot rolling, the C-Mn steel pipes were inspected in ultrasound equipment to detect, internal noise caused by phosphorus embrittlement. In these pipes were taken samples for characterization of the inner surface and cross section using optical microscope and scanning electron microscope. In these strips were found in some regions that were embrittlement by phosphorus, where embrittlement was present in the grain boundary and regions with presence of molten salt corrosion caused by phosphorus. Simulations of the embrittlement of phosphorus in the process were performed on a laboratory scale. The results shown that when increases the amount of deoxidizer and the expose time of steel with deoxidizer, increases the thickness of the phosphorus layer and when increase the temperature the molten salt corrosion becomes more significant. In addition, the present work confirmed that phosphorus has a tendency to segregate at grain boundaries, leading to intergranular fracture. Another important result that was found in the present work was that deoxidizers containing silica in their chemical composition present less amount of phosphorus diffused in steel. The silicon forms a protective layer of faialite (Fe2SiO4) that separates the substrate (steel) from phosphorus. Thus, the penetration of phosphorus in steel decreases and in this case the embrittlement of steel by phosphorus is lower. In the Thermo-Calc and Matlab program, it was demonstrated that the effective coefficient of diffusion of phosphorus increases with increasing temperature and the time of exposure with the deoxidizer. In addition, it has been shown that the increases the phosphorus content induce the liquid phase formed at lower temperatures and the percentage of phosphorus in the eutectic phase and liquid phase increase.